2018
DOI: 10.1002/jlb.3mr0318-086rr
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental signals govern the cellular identity of testicular macrophages

Abstract: Testicular macrophages (TM) comprise the largest immune cell population in the mammalian testis. They are characterized by a subdued proinflammatory response upon adequate stimulation, and a polarization toward the immunoregulatory and immunotolerant M2 phenotype. This enables them to play a relevant role in supporting the archetypical functions of the testis, namely spermatogenesis and steroidogenesis. During infection, the characteristic blunted immune response of TM reflects the need for a delicate balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 113 publications
(283 reference statements)
0
49
0
Order By: Relevance
“…In both rodents and humans, macrophages represent the largest population of immune cells in the testis and play a key role in maintaining testis immune privilege (457,485). Rodent and primate testis macrophages display an M2-like phenotype.…”
Section: The Role Of Resident Immune Cells In the Immune Privilege Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In both rodents and humans, macrophages represent the largest population of immune cells in the testis and play a key role in maintaining testis immune privilege (457,485). Rodent and primate testis macrophages display an M2-like phenotype.…”
Section: The Role Of Resident Immune Cells In the Immune Privilege Ofmentioning
confidence: 99%
“…In response to infection or inflammatory stimuli, rodent testis macrophages exhibit relatively low inflammatory responses and high immunosuppressive properties compared with macrophages located in others tissues (reviewed in (457)), which confer upon them a unique immune-tolerant role against meiotic germ cells antigens that egress from seminiferous tubules. Blocked NF-kB signaling pathway and basal corticosterone production in rat testicular macrophages is associated with reduced pro-inflammatory capacities (457). In the mouse, interstitial embryo-derived macrophages have more potent immune suppressive properties than peritubular macrophages, which are derived from the bone marrow after birth (484).…”
Section: The Role Of Resident Immune Cells In the Immune Privilege Ofmentioning
confidence: 99%
“…For instance, reliance on mir-511-3p targeting does not allow for precise differentiation between M2 macrophages and moDCs, or the relative contribution of both cell types in ZIKV infection of the testicular interstitium. Macrophages (M2 macrophages in particular) are the most abundant leukocyte population in the mammalian testes [27,66]. For primates, it was shown that M2 macrophages expressing CD169 marker are~200 times more abundant compared to all subtypes of testicular DCs [23].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…It was recently shown that primary human Leydig cells fail to support efficient ZIKV replication in cell culture [25,26]. In contrast, studies of IFN-receptor deficient mice and human testicular explants demonstrated that ZIKV can infect macrophages, which constitute the most abundant group of testicular leukocytes [23,27], rather than myoid or Leydig cells [19,28]. These studies suggest that testicular macrophages may be the primary target for early ZIKV infection in the testicular interstitium.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are characterized by a subdued proinflammatory response, a polarization toward the immunoregulatory and immunotolerant phenotype that enables them to play a relevant role in the functions of the testis. During infection, the characteristic blunted immune response of tissue macro-phages reflects the need for a delicate balance between a sufficiently strong reaction to counteract invading pathogens, and the prevention of excessive proinflammatory cytokine levels with the potential to disturb or destroy spermatogenesis (Meinhardt et al, 2018). The content of CD11b+ cells remained elevated over a period of observation.…”
Section: Discussionmentioning
confidence: 99%